Clinical indicators of wound infection and biofilm: reaching international consensus. (2nd March 2019) - Haesler, Emily; Swanson, Terry; Ousey, Karen; Carville, Keryln
Abstract : Objective: To achieve international consensus relating to clinical indicators for a chronic wound, wound infection and biofilm presence to inform the development of international clinical guidance for assessing and managing wound infection. Method: An online Delphi consensus process of international key opinion leaders in infection was undertaken. A literature search underpinned the development of issue statements related to terminology, emerging topics and debate in the field of wound infection. Experts participated in three rounds of consensus voting, sharing their opinions and indicating their level of agreement with the issue statements. Votes were calculated using web-based software that implements a nominal group voting methodology previously published by Research and Development/University of California at Los Angeles. Results: A total of 14 experts took part in the development process. Consensus was reached on clinical indicators of wound chronicity, wound infection and biofilm presence. Agreement was also reached that the term 'critical colonisation' should no longer be used to refer to a stage in the wound infection continuum. Conclusion: Outcomes from the consensus process were used to inform the development of international, evidence-informed guidance on the assessment and treatment of wound infection to promote improved outcomes for people with wounds.